With Our Hands The Story of Carpenters in Massachusetts - Erlich, Mark (Temple University Press, 1986)
Mark Erlich wrote With Our Hands: The Story of Carpenters in Massachusetts, his history of the carpentry trade in Massachusetts, during an extraordinarily creative period in U.S. labor studies. The late 1970s saw the National Endowment for the Humanities and its state councils sponsoring ambitious public projects focused on labor unions, working-class culture, and community history. Two years after a diisplay commemorating the centenial of the United Brotherhood of Carpenters and Joiners of America appeared in the union's headquarters in Washington DC, Erlich, a journeyman carpenter in Boston's Local 40, took up a new task: to research and narrate the lively hundred-year history of the carpenters union in Massachusetts, on the job, at the union hall, and in its busiest communities. Erlich built his work around everyday themes of work, family, and community. He documented and interpreted U.S. labor history along new lines, with less emphasis on institutions and more interest in working-class continuity via the union's own stories. Erlich was determined that the reader would feel these histories as his or her own, achieved through his comprehensive narratives highlighted by vintage photos, historic documents, and excerpts from oral histories. The numerous photos allow glimpses of construction in the making, from building sites at their foundations, to a solitary worker climbing the laminated beams of an arched church roof, to a series of complicated interior angles of the "T" subway extension beneath the streets of Cambridge and Somerville.